Characterization of transgenic mouse models targeting neuromodulatory systems reveals organizational principles of the dorsal raphe - Daniel F. Cardozo Pinto (Nature Portfolio, 2019)
In addition to serotonin neurons, the dorsal raphe nucleus (DR) also contains dopamine, glutamate, and GABA neurons. Here, the authors systematically compare the neurochemical identity, cell type specificity, anatomical distribution, and connectivity of DR cells targeted by commonly used Cre lines.